Poor sleep quality and associated factors among undergraduate students: a single-university cross-sectional study: 10.55131/jphd/2024/220317 - Sanguankittiphan, Pariyakorn; Taejarernwiriyakul, Ormjai; Khuancharee, Kitsarawut (Journal of Public Health and Development, 2024)
Poor sleep quality is a global health concern. It leads to reduced cognitive abilities and delayed reactions, which negatively affect students’ ability to study and contribute to health-related issues such as depression, obesity, cardiovascular disease, and accidents. This study aims to estimate the rate of poor sleep quality among Thai undergraduate students and identify the factors associated with poor sleep quality. A cross-sectional study was conducted using self-administered questionnaires that included questions on demographic data, caffeine consumption, stress levels, health status, sleep behavior, and sleep quality measured by the Pittsburgh Sleep Quality Index (PSQI). The participants comprised 609 students from different faculties who were enrolled at the university. The factors related to poor sleep quality were analyzed using a multiple logistic regression model. The overall rate of poor sleep quality was 66.3% (95% CI [62.4, 70.1]). Multivariate analysis showed that poor sleep quality was significantly associated with high and severe stress levels (AOR = 4.51; 95% CI [2.53, 8.03]), weak and very weak overall physical health in the previous month (AOR = 1.87; 95% CI [1.03, 3.38]), and physical illnesses in the previous month (AOR = 1.64; 95% CI [1.04, 2.57]). The present study found that being stressed was associated with poor sleep quality. Stress management and lifestyle modifications are highly recommended for undergraduate students to enhance their sleep quality.